The role of website quality, perceived value, and consumer satisfaction on repurchase intentions of Indonesian railway tickets - Resti Febrianti; Tuti Asmala; Ahmad Johan (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to determine the role of website quality, perceived value, and consumer satisfaction on the repurchase intention of Indonesian railway tickets.Method — This research employs a quantitative methodology to investigate the causal links between variables. This study's sample consisted of 100 consumers of Indonesian railway tickets in Bandung who were randomly selected through the distribution of questionnaires and subsequently analyzed using regression analysis with the assistance of the Smart PLS software.Result — This study's findings reveal that three criteria, namely website quality, perceived value, and customer satisfaction, substantially impact the repurchase intentions of Indonesian rail ticket purchasers.Contribution — This study has implications for businesses, which should present information through their websites and provide excellent customer service to boost perceived value. In addition, the interactions carried out in the provision of services must address all client concerns so that consumers are pleased with the services rendered.